PEMETAAN PENELITIAN PERPAJAKAN : KEPATUHAN WAJIB PAJAK UMKM BERDASARKAN UU NOMOR 7 TAHUN 2021 - Nur Hayati; Nadia Ayu Rahmanda; Yulia Isnaini Hafifah; Putri Lailia Fitri; Elza Safitri (Jurnal Liabilitas, 2024)
This research aims to provide an overview of MSME taxpayer compliance in accordance with Law Number 7 of 2021 and to find out what factors influence MSME taxpayer compliance and provide a reference regarding MSME taxpayer compliance which can later be used as a research evaluation method in the field of taxation regarding subsequent MSME taxpayer compliance. The methodology used in this research is a literature review using narrative and descriptive techniques. The research results showed that there were 31 articles sourced from Sinta indexed journals for the 2021-2023 period. From the mapping that has been carried out, the research topic regarding taxpayer compliance dominates with 21 articles, while MSME taxpayer compliance has 9 articles, and Law Number 7 of 2021 has 1 article. Most researchers use quantitative methods as the basis of their research.